Construction of hierarchical porous carbon with mesopores-enriched from sodium lignosulfonate by dual template strategy and their diversified applications for CO2 capture, radioactive iodine adsorption, and RhB removal. Issue 6 (December 2022) - Shao, Lishu; Wan, Huan'ai; Wang, Lizhi; Wang, You; Liu, Na; Wu, Zhiping; Luo, Weihua; Zhan, Peng; Zhang, Lin; Huang, Jianhan
Abstract: Lignosulfonate, as the large-scale by-products from the sulfite pulping, converting them to porous carbon is an alternative potential path. However, most sodium lignosulfonate (LS-Na) derived porous carbon all belonged to the dominated microporous carbon materials, and had poor graphitization degree and low heteroatoms content. Here, a series of hierarchically porous carbon with rich and controllable mesopores were firstly prepared from LS-Na by two dual template strategies. These carbon materials showed high Brunauer-Emmett-Teller (BET) surface areas (SBET ) of 230.6–1483.3 m 2 /g, hierarchical porous structure (mesopore content up to 84.5%), rich heteroatoms (N, O, S) doping (9.22–22.53%), and good graphitization structure. The incorporation of SBA-15 and Ni species as the nano-templates not only brought the unique micro-structure, but also enhanced mesoporous properties. SLS-C had the largest CO2 uptake (206.2 mg/g) due to the largest micropore volume (Vmicro ) and ultramicropore volume (Vultra ) by micropore filling mechanism. SLS-S-Ni-C possessed effective iodine capacity (∼2.2 g/g) and good recycling (∼90.9%), the adsorption process was based on the dominated physical adsorption, meanwhile, also along with the weak chemical interaction for some iodine molecules by little strong binding sites. SLS-Ni-C had the largest equilibrium capacity of RhB (350.6 mg/g) and the fast adsorption kinetic (about 50 min) due to the large SBET, suitable micro-mesopores size and proportion. This work provided a kind of hierarchical porous carbon from LS-Na by dual template routes, and matched adsorbents for the removal of targeted contaminants. Graphical Abstract: ga1 Highlights: LS-Na derived hierarchically mesoporous carbon obtained by dual template strategies. They showed high SBET, hierarchical pores (mesopore: 84.5%), and rich heteroatoms. SBA-15 and Ni species brought unique micro-structure and well mesoporous properties. These adsorbents were offered for the removal of CO2, iodine vapor, and Rhodamine B. The adsorption mechanism and the relationship of structure-properties were discussed.